2017
DOI: 10.1186/s40168-017-0369-0
|View full text |Cite
|
Sign up to set email alerts
|

Catalogue of antibiotic resistome and host-tracking in drinking water deciphered by a large scale survey

Abstract: BackgroundExcesses of antibiotic resistance genes (ARGs), which are regarded as emerging environmental pollutants, have been observed in various environments. The incidence of ARGs in drinking water causes potential risks to human health and receives more attention from the public. However, ARGs harbored in drinking water remain largely unexplored. In this study, we aimed at establishing an antibiotic resistome catalogue in drinking water samples from a wide range of regions and to explore the potential hosts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
124
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(129 citation statements)
references
References 46 publications
4
124
1
Order By: Relevance
“…Metagenomic analyses of drinking water across 25 cities on three continents show a wide diversity of ARG types in human drinking supplies with the majority of samples having higher ARG abundance than environmental sediment and soil samples. 60 Altogether these studies illustrate the ubiquitous presence of AROs and ARGs in water supplies and the importance of understanding the origin and spread of ARGs in drinking water. Unless monitored and mediated, ARO and ARG environmental reservoirs can contribute to a vicious cycle that spreads AROs and ARGs over time and vast distances ( Figure 2).…”
Section: Using Metagenomics To Monitor Environmental and Biological Rmentioning
confidence: 93%
See 1 more Smart Citation
“…Metagenomic analyses of drinking water across 25 cities on three continents show a wide diversity of ARG types in human drinking supplies with the majority of samples having higher ARG abundance than environmental sediment and soil samples. 60 Altogether these studies illustrate the ubiquitous presence of AROs and ARGs in water supplies and the importance of understanding the origin and spread of ARGs in drinking water. Unless monitored and mediated, ARO and ARG environmental reservoirs can contribute to a vicious cycle that spreads AROs and ARGs over time and vast distances ( Figure 2).…”
Section: Using Metagenomics To Monitor Environmental and Biological Rmentioning
confidence: 93%
“…One common strategy of looking for ARGs is to use the primary nucleotide or amino acid sequence of known or putative ARGs. 24,56,59,60,68 These methods most commonly work by aligning a query sequence to known ARGs or markers from a curated database (Figure 3, top). [64][65][66][67] Sequence-based methods can be performed rapidly and in a massively parallel manner compared with culture-based methods of resistance determination.…”
Section: Sequence-based Methodsmentioning
confidence: 99%
“…In addition to chemical EPs, ARGs have also been found in drinking water systems. 181 ARG subtypes were detected with an abundance range of 2.8 × 10 2 to 4.2 × 10 1 copies of ARG per cell in the drinking water samples collected from 25 cities in mainland China, Hong Kong, Macau, Taiwan, South Africa, Singapore and the USA (Ma et al 2017b).…”
Section: Occurrence Of Eps In Water Environmentsmentioning
confidence: 99%
“…In recent years, the occurrence of ARB and ARGs in drinking water were investigated more and more frequently [5][6][7], as it was revealed that resistance to antibiotics is often correlated with resistance to disinfectants [8,9] (however, it is worth to note that this hypothesis is still controversial, as it was stated by Lin et al [10]) and metals [11], therefore making water treatment plants (WTPs) and tap water distribution systems a niche for ARB dwelling and proliferation.…”
Section: Introductionmentioning
confidence: 99%